Teachers’ Politeness Markers in Request in Classroom Interactions (NOBEL: Journal of Literature and Language Teaching, 2020)
This study is an attempt to examine politeness markers employed by Indonesian English teachers in classroom interactions. Purposefully chosen English teachers were observed, audio-recorded, and analyzed by using the politeness principle and Gricean cooperative principle. The conversation analysis revealed that to mitigate the illocutionary act of request, aside from using internal modifiers at most (consultative device, politeness markers, hesitators, hedges, play-downs, committers, down-toners, understaters), the teachers also used external devices as an adjunct to the head acts (grounder, sweetener, and disarmer). Besides, teachers intentionally violated the maxim for the sake of extending the talk. Further research needs to include more participants and instruments in a wider area of analysis.